Optimization of Savonius Turbine Performance with Variations in Blade and Shaft Spacing on the Coast of Sarmi Regency, Papua Province - Numberi, Johni Jonatan; Joni; Allo, Obed Rante; Griapon, Nourish C.; Ansanay, Yane A.; Ramandei, Lazarus; Wanane, Wilfriedf; Allo, Rombe; Manalu, Janviter; Safanpo, Apolo; Hartiningsi, Endang; Liga, Marthen; Karapa, Enos; Lefaan, Yosef; Setiadji, Prihananto; Innah, Herbert (Fakultas Teknik Universitas Pancasila, 2024)
The use of wind energy as one of the producers of electrical energy is done by converting mechanical energy into electrical energy from wind turbines, one of which is the savonius wind turbine. Savonius wind turbines in use are able to work at low wind speeds. This study aims to evaluate the potential of wind energy that can be generated by optimization in savonius wind turbines by measuring the power generated by varying the gap distance between Balde and turbine shafts and analyzing the most optimal power as a source of power generation on the coast of Sarmi Regency, Papua Province. The analysis method in this study is field surveys, wind speed measurements, power optimization, BHP and tool efficiency carried out with variations in the distance between the blade and turbine shaft, namely 5 cm, 10 cm and 15 cm. The results of this study stated that the most optimal and stable results on the power generated by the turbine as well as the BHP value and the best tool efficiency were a distance variation of 15 cm with an average power value produced (P0) of 15.55 Watts, an average BHP value of 0.56 Watts and an average efficiency value of 7.59%.